ANALISIS POLA BELANJA PENGUNJUNG MAL DENGAN ALGORITMA APRIORI - Riyadi, Andri Agung (LPPM Universitas Nusa Mandiri, 2018)
XYZ Mall was established in 2013 in the coastal area of Jakarta by offering advantages that other malls do not have, namely the location which is directly facing the sea or the bay of Jakarta. Tenants who are interested in opening a store or shop at XYZ Mall are also selected according to the needs of visitors. The application of the Apriori Algorithm is expected to assist in providing useful information for increasing the number of visitors and selling products from tenants in XYZ Mall. Implementations using the Apriori Algorithm can help management in decision-making policies regarding what is related to the acceptance of prospective tenants or the placement of tenant locations in the mall. In this work, the apriori algorithm was successfully applied in the search for shopping patterns of mall visitors. The results obtained with apriori algorithm, one of which is the highest combination of confidence is the pattern if spending in the General category tenants will spend in the Food And Beverage category tenant with a confidence of 50%.